Potential factors involved in the early pathogenesis of Streptococcus uberis mastitis: a review - Fessia, Aluminé S; Odierno, Liliana M (Folia microbiologica, 2021)
Bovine mastitis is an inflammation of the mammary gland, which could be the result of allergy, physical trauma, or invasion by pathogens as Streptococcus uberis. This pathogen is an environmental pathogen associated with subclinical and clinical intramammary infection (IMI) in both lactating and non-lactating cows, which can persist in the udder and cause a chronic infection in the mammary gland. In spite of the important economic losses and increased prevalence caused by S. uberis mastitis, virulence factors involved in bacterial colonization of mammary glands and the pathogenic mechanisms are not yet clear. In the last 30 years, several studies have defined adherence and internalization of S. uberis as the early stages in IMI. S. uberis adheres to and invades into mammary gland cells, and this ability has been observed in in vitro assays. Until now, these abilities have not been determined in vivo challenges since they have been difficult to study. Bacterial surface proteins are able to bind to extracellular matrix protein components such as fibronectin, collagen and laminin, as well as proteins in milk. These proteins play a role in adhesion to host cells and have been denominated microbial surface components recognizing adhesive matrix molecules (MSCRAMMs). This article aims to summarize our current knowledge on the most relevant properties of the potential factors involved in the early pathogenesis of S. uberis mastitis.
Keywords: rizikové faktory; Cattle; Animals; Mammary Glands, Animal; skot; mléčné žlázy zvířat; Risk Factors; Female; zvířata; mléko; Streptococcus; Mastitis, Bovine; mastitida skotu; Streptococcal Infections; streptokokové infekce; ženské pohlaví; Milk